2015
DOI: 10.1177/1754073915601226
|View full text |Cite
|
Sign up to set email alerts
|

A Sociological Perspective on Emotions in the Judiciary

Abstract: Introducing a sociological perspective on judicial emotions, we argue that previous studies underemphasize structural and interactional dimensions. Through key concepts in the sociology of emotions we relate professional court actors’ emotion management to the emotional regime of the judiciary. Examples from the Swedish judiciary illustrate three main arguments: (a) The idea of rational justice as nonemotional must be investigated as a joint accomplishment including collective emotion management; (b) Judicial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“…Research indicates that the inhibition of facial synchrony can be a strategy for distancing oneself from social targets and maintaining an independent stance (Seibt, Mühlberger, Likowski, & Weyers, ). Professional judges engage in quite extensive emotion management, and, indeed, attempt to prevent facial emotional displays when observing oral testimonies in court to maintain an impartial demeanour (Bergman Blix & Wettergren, ). The current findings show that such a strategy may in fact introduce a new kind of bias, reducing perceived credibility overall.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that the inhibition of facial synchrony can be a strategy for distancing oneself from social targets and maintaining an independent stance (Seibt, Mühlberger, Likowski, & Weyers, ). Professional judges engage in quite extensive emotion management, and, indeed, attempt to prevent facial emotional displays when observing oral testimonies in court to maintain an impartial demeanour (Bergman Blix & Wettergren, ). The current findings show that such a strategy may in fact introduce a new kind of bias, reducing perceived credibility overall.…”
Section: Discussionmentioning
confidence: 99%
“…I use the term “emotional regime” to refer to “the rule-bound and controlled set of institutional norms which enable power to be exercised in ordered ways within a framework of civility” (Harris 2011b). The subtlety of the Swedish courtroom and its emotional regime has been described (Bergman Blix and Wettergren 2016; Flower 2014a) as viewing “emotion as disruptive of rationality” (Bergman Blix and Wettergren 2016, 34), so emotions should remain appropriately managed. Swedish gestures are typically subtle: facial expressions and gestures are often smaller and less intense compared to other cultures (Allwood 1999; see also Hägg 2004).…”
Section: The Swedish Courtroom: An Emotional Regime Of Control and Sumentioning
confidence: 99%
“…The importance of professional emotion management in close interactions is evident in some cases, such as physicians who need to recognise and adapt to patients' emotions in order to arrive at correct and efficient diagnoses and treatments (Larson & Yao, 2005;Lee, Lovell, & Brotheridge, 2010). But emotion management is also an important feature in other types of professional interactions, for example to legal actors during court hearings (Bergman Blix & Wettergren, 2015;Maroney & Gross, 2014).…”
Section: Managing Emotions In Professional Lifementioning
confidence: 99%
“…Legal actors need to tone down emotional expressions to fit with norms of neutrality. A study on the Swedish judiciary found that a common way for judges to express irritation was to put down their pen-signalling that the other legal professionals should move on (Bergman Blix & Wettergren, 2015). Their experience of irritation could be strong, but their expression was adjusted to fit with norms of professionalism.…”
Section: Conclusion and Applicability For Other Professionsmentioning
confidence: 99%